MdATG5a induces drought tolerance by improving the antioxidant defenses and promoting starch degradation in apple. (November 2021) - Jia, Xin; Jia, Xumei; Li, Tiantian; Wang, Yu; Sun, Xun; Huo, Liuqing; Wang, Ping; Che, Runmin; Gong, Xiaoqing; Ma, Fengwang
Highlights: The expression of MdATG5a was induced by drought and oxidative stress. Overexpression of MdATG5a enhanced drought tolerance in apple, as indicated by less drought-related damage. MdATG5a overexpression improved antioxidant defenses in apple under drought stress. Overexpression of MdATG5a promoted the degradation of starch in response to drought stress. Abstract: Drought occurrence seriously affects the productivity and quality of apple crop worldwide. Autophagy, a conserved process for the degradation and recycling of unwanted cellular components, is considered to positively regulate the tolerance of various abiotic stresses in plants. In the current study, we isolated two ATG5 homologs genes, namely, MdATG5a and MdATG5b, from apple, demonstrating their responsiveness to drought and oxidative stresses. In addition to having the same cellular localization in the nucleus and cytoplasm, both MdATG5a and MdATG5b could interact with MdATG12. Transgenic apple plants overexpressing MdATG5a exhibited an improved drought tolerance, as indicated by less drought-related damage and higher photosynthetic capacities compared to wild-type (WT) plants under drought stress. The overexpression of MdATG5a improved antioxidant defenses in apple when exposed to drought via elevating both antioxidant enzyme activities and the levels of beneficial antioxidants. Furthermore, under drought stress, the overexpression of MdATG5a promoted the mobilization of starch to accumulate greater levels of soluble sugars, contributing to osmotic adjustments and supporting carbon skeletons for proline synthesis. Such changes in physiological responses may be associated with increased autophagic activities in the transgenic plants upon exposure to drought. Our results demonstrate that MdATG5a -mediated autophagy enhances drought tolerance of apple plants via improving antioxidant defenses and metabolic adjustments.